Psychological Vulnerability Indices and the Adolescent's Good Mental Health Factors: A Correlational Study in a Sample of Portuguese Adolescents - Joana Nobre; Henrique Luis; Ana Paula Oliveira; Francisco Monteiro; Raul Cordeiro; Carlos Sequeira; Carme Ferré-Grau (MDPI AG, 2022)
Background: Psychological vulnerability (PV) indicates the individual's inability to adapt to stressful situations. Adolescents experience negative impacts on their future mental health if they do not acquire the skills and knowledge necessary to have good mental health during their developmental stage. Aim: To compare the PV index among the three stages of adolescence and to explore the factors involved in good mental health, including the relationship between adolescents' PV indices and sociodemographic variables, and the relationship between adolescents' PV index and their knowledge of the factors that characterize good mental health. Method: An exploratory, cross-sectional, correlational study was carried out in three public schools in a region of Portugal, using online self-completed questionnaires: the Psychological Vulnerability Scale (PVS) and the Mental Health-Promoting Knowledge (MHPK-10). Results: Our convenience sample consisted of 260 adolescents, with a mean age of 14.07 years who were students between 5th and 12th grades, mostly female. Moderate PV indexes were obtained that were higher in late adolescence, i.e., in older adolescents, who were females in a more advanced school year, with worse self-perceptions of their physical and mental health and body image, and who frequently used a health service due to mental health problems. The association between the PV index and the level of knowledge about the factors involved in good mental health did not reach a statistical significance (p = 0.06). Conclusions: These results suggest a need for a design of personalized interventions that promote adolescents' mental health literacy, that prevent PV, and that should be initiated in early adolescence.